PENGEMBANGAN LEMBAR KEGIATAN SISWA MATERI LUAS BANGUN DATAR BERBASIS METODE PEMBELAJARAN DISCOVERY UNTUK SISWA SEKOLAH MENENGAH PERTAMA - Rohman Rohman; Riya Dhotul Janah (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2015)
This research aims to develop the student activity sheet material broad flat wake discovery based learning methods for secondary school students are valid and practical and how the potential effect of the use of student activity sheet based discovery learning method for junior high school students. The method used is a method of research and development (development research). Stages of development research done of the preliminary phase which includes the analysis and prototyping stage (designing) and evalution formative stages which include self evalution, expert reviews, one to one, small group, and a field test. Based on the results of the analysis of the product, obtained LKS discovery based learning methods are valid and praktis.Valid seen from the results of expert assessment is based on content, construct, and languages. Practical seen from the observations of the trial small group where students can complete a given student activity sheet. Based on the results and final grades on students' ability test VII.1 SMP Negeri 3 Palembang done individually than 35 students that there were 15 (42.85%) of students categorized as very good and 20 (57.14%) students including both categories. Overall average grade student ability VII.1 is 78.85 which means that the learning outcomes of students belonging to either category. Based on the analysis of student learning outcomes, it can be concluded that student activity sheets that have been developed have potent